A study of entrepreneurial intention among Malaysian university students - Chan, Chi Yan; Low, Ee Ling; Yu, Lai Ying (2017)
This study focuses on university students’ behavioral intention towards entrepreneurship. Research questions and four hypotheses are exploit and tested to achieve the research project objectives. Furthermore, the hypothesis that have been developed is measured accordingly and the results obtained are subsequently explained. This research also comprises of literature review to develop a clearer picture about each independent variable as well as dependent variable in terms of definition, characteristics and relationships. Moreover, a sample size of 300 had been collected for this research by using random sampling method. The questionnaires were distributed by travel agency to the target respondent who have been purchase a cruise package before. Data gathered from the survey questionnaires are able to analyze by using Statistical Package Social Science (SPSS) version 22.0. The result will then be discussed in tables and charts. In addition, major findings of this research project were discussed in order to understand the relationship between attitudes toward behavior, subjective norms, perceived behavioral control, and entrepreneur education and entrepreneur intention of university students. After conducting this research, the empirical results revealed attitude toward behavior and perceived behavioral control have a positive significance relationship on entrepreneur intention. On the other hand, subjective norms and entrepreneur education have a negative relationship on entrepreneur intention. Last but not least, this research project also include managerial implications to provide insightful and useful information. While the limitations confront in this research project will be addressed. Besides that, recommendation will also be developed to provide assistance for future researchers in dealing with these limitations.